Positive electrode active material, secondary battery, and electric device

By adding specific proportions of nickel, cobalt, manganese and other elements and modified elements to the positive electrode active material of lithium-ion batteries, combined with a single crystal polycrystalline structure, the problem of the decrease in electrochemical stability when the material is increased is solved, and the problem of the material being reduced in energy density is achieved. High capacity and long cycle life.

CN119297273AActive Publication Date: 2025-01-10CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411584887.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-05
Filing Date
2024-11-07
Publication Date
2025-01-10
Estimated Expiration
2044-11-07

AI Technical Summary

Technical Problem

While the existing lithium-ion battery positive electrode active materials increase the energy density, the electrochemical stability performance decreases, making it difficult to take into account high capacity and long cycle life.

Method used

Using a positive electrode active material containing transition metal elements, the molar proportion of nickel, cobalt and manganese elements is more than 55%, and the proportion of cobalt is less than 20%, and Zr, Al, B, Nb, Mo, W is added. The structural stability of the material and lithium ion transmission are optimized through the mass ratio of different modified elements, combined with the structure of single crystal and polycrystalline particles.

Benefits of technology

It significantly improves the energy density and cycling performance of the material, achieves a balance of high capacity and long cycle life, and enhances electrochemical activity and power performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297273A_ABST
    Figure CN119297273A_ABST
Patent Text Reader

Abstract

The invention provides a positive electrode active material, a secondary battery and an electric device, the positive electrode active material comprises: a nickel element, the molar ratio of the nickel element in the total amount of nickel, cobalt and manganese metal elements being 55% or more; the molar ratio of the cobalt element in the total amount of the nickel, cobalt and manganese metal elements is less than 20%; a first modifying element Zr; a second modifying element Al; a third modifying element B; and the fourth modifying element is at least one of Nb, Mo and W. The positive electrode active material provided by the invention has excellent performance, and the battery prepared from the positive electrode active material has good energy density and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to a positive electrode active material, a secondary battery and an electrical device. Background Art

[0002] With the escalation of energy crisis and environmental problems, it is urgent to develop green, low-carbon and environmentally friendly new energy. As an electrochemical energy storage device, lithium-ion batteries have the advantages of large capacity, no memory effect and wide application window, and have been widely used in various fields. In the field of transportation, new energy vehicles with lithium-ion batteries as power units are gradually replacing traditional fuel vehicles and becoming the preferred means of transportation for people in various countries. The positive electrode active materials commonly used in the industry, such as lithium iron phosphate, medium and low nickel ternary materials, etc., cannot meet the needs of end customers due to the performance limitations of the materials themselves. Summary of the invention

[0003] The present application is made in view of the above-mentioned problems, and its purpose is to stabilize the crystal structure of the positive electrode active material by modifying the positive electrode active material with multiple elements, so that the material has the advantages of high energy density and structural stability, and the battery prepared therefrom can have both good energy density and cycle performance.

[0004] In order to achieve the above-mentioned purpose, the first aspect of the present application provides a positive electrode active material containing transition metal elements, wherein the positive electrode active material includes: a nickel element, wherein the molar proportion of the nickel element in the total amount of nickel, cobalt and manganese elements is more than 55%; a cobalt element, wherein the molar proportion of the cobalt element in the total amount of nickel, cobalt and manganese elements is less than 20%; a first modifying element Zr; a second modifying element Al; a third modifying element B; and a fourth modifying element: which is at least one of Nb, Mo and W; wherein, based on the total mass of the positive electrode active material, the mass proportion of the first modifying element is 0.01% to 0.5%, the mass proportion of the second modifying element is 0.01% to 1%, the mass proportion of the third modifying element is 0.01% to 0.4%, and the mass proportion of the fourth modifying element is 0.01% to 2.2%.

[0005] In ternary materials, as the proportion of nickel content in transition metals increases, the energy density of the material becomes higher and higher, but the higher energy density reduces the electrochemical stability of the material. In the technical solution of the present application, by adding modifying elements to the ternary material and coupling a variety of different modifying elements with the ternary material, the capacity and cycle performance of the ternary material can be greatly improved. Among them, the first modifying element and the second modifying element can react with the bulk phase of the ternary material, which helps to improve the structural stability of the material and optimize the transmission of lithium ions, and also helps to reduce the side reactions between the ternary material and the electrolyte, thereby significantly improving the cycle stability and power performance of the material. At the same time, the third modifying element and the fourth modifying element can increase the capacity of the material, so that the ternary material can achieve high capacity. When the mass ratio of these four modifying elements is matched with each other within the above range, the positive electrode active material can take into account both good capacity and stability, and the battery prepared therefrom can take into account both good energy density and cycle performance.

[0006] In any embodiment, in the positive electrode active material, the mass ratio of (first modifying element+second modifying element):(third modifying element+fourth modifying element) is 1:(0.1-10).

[0007] In any embodiment, in the positive electrode active material, the mass ratio of (first modifying element+second modifying element):(third modifying element+fourth modifying element) is 1:(0.1-0.5).

[0008] In any embodiment, in the positive electrode active material, the mass ratio of (element Zr+element Al): (element B+element W) is 1:(0.1-0.5).

[0009] In any embodiment, in the positive electrode active material, the mass ratio of the first modifying element: the second modifying element is 1:(0.1-30).

[0010] In any embodiment, in the positive electrode active material, the mass ratio of the first modifying element: the second modifying element is 1:(0.1-1).

[0011] In any embodiment, in the positive electrode active material, the mass ratio of the element Zr to the element Al is 1:(0.1-1).

[0012] In any embodiment, in the positive electrode active material, the mass ratio of the third modifying element: the fourth modifying element is 1:(0.05-30).

[0013] In any embodiment, in the positive electrode active material, the mass ratio of the third modifying element: the fourth modifying element is 1:(0.1-1).

[0014] In any embodiment, in the positive electrode active material, the mass ratio of element B:element W is 1:(0.1-1).

[0015] By further precisely controlling the mass ratios of the first modifying element, the second modifying element, the third modifying element, and the fourth modifying element, the electrochemical properties and stability of the positive electrode active material can be further optimized to achieve the optimal solution for the comprehensive performance of the material.

[0016] In any embodiment, based on the total mass of the positive electrode active material, the mass proportion of the first modifying element is 0.05% to 0.5%.

[0017] In any embodiment, based on the total mass of the positive electrode active material, the mass proportion of the second modifying element is 0.05% to 0.3%.

[0018] In any embodiment, based on the total mass of the positive electrode active material, the mass proportion of the third modifying element is 0.01% to 0.2%.

[0019] In any embodiment, based on the total mass of the positive electrode active material, the mass proportion of the fourth modifying element is 0.01% to 0.3%.

[0020] When the mass ratios of the first modifying element, the second modifying element, the third modifying element, and the fourth modifying element are within the above ranges, the energy density and cycle performance of the material can be further improved.

[0021] In any embodiment, the molar proportion of the nickel element in the total amount of nickel, cobalt and manganese elements is 60% to 95%; and / or the molar proportion of the cobalt element in the total amount of nickel, cobalt and manganese elements is 3% to 10%.

[0022] In any embodiment, the molar ratio of the nickel element in the total amount of nickel, cobalt and manganese metal elements is 80% to 95%.

[0023] When the ratio of nickel and cobalt to transition metal in the positive electrode active material is within the above range, the material has a better gram capacity, and the battery prepared therefrom can better balance energy density and cycle performance.

[0024] In any embodiment, the positive electrode active material includes single crystal particles and polycrystalline particles.

[0025] When the positive electrode active material includes both single crystal particles and polycrystalline particles, compared with a single particle type system, the single crystal mixed polycrystalline system is beneficial to further improve the compaction density of the material and improve its volume energy density and cycle stability.

[0026] In any embodiment, the specific surface area of ​​the single crystal particles is 0.9 to 1.5 m 2 / g, the specific surface area of ​​the polycrystalline particles is 0.3 to 1.0 m 2 / g.

[0027] When the specific surface area of ​​the positive electrode active material is within the above range, it is beneficial to increase the contact area between the positive electrode material and the electrolyte, so that the electrochemical activity of the material is further enhanced.

[0028] In any embodiment, in the positive electrode active material, a mass ratio of the single crystal particles to the polycrystalline particles is 1:9 to 5:5.

[0029] In any embodiment, the volume average particle size Dv50 of the single crystal particles is 3 to 5 μm, and the volume average particle size Dv50 of the polycrystalline particles is 4 to 13 μm.

[0030] When the single crystal particles and the polycrystalline particles in the positive electrode active material are matched in the above-mentioned mass ratio and particle size, the energy density and cycle performance of the battery can be further improved.

[0031] In any embodiment, the positive electrode active material has a molecular formula Li a (Ni b Co c Mn 1-b-c ) 1-x-y-z- q Zr x Al y B z Q q O e , wherein Q includes at least one of Nb, Mo, and W, 0.9≤a≤1.2, 0.55≤b≤0.95, 0≤c≤0.20, 1.8≤e≤2.2, 0 <x≤0.04,0<y≤0.02,0<z≤0.09,0<q≤0.03。

[0032] In any embodiment, the positive electrode active material further includes strontium (Sr), and the mass proportion of the strontium element is 0.05% to 0.2% based on the total mass of the positive electrode active material.

[0033] In any embodiment, the positive electrode active material further includes yttrium (Y), and based on the total mass of the positive electrode active material, the mass proportion of the yttrium is 0.05% to 0.2%.

[0034] Further adding modifying elements such as strontium and / or yttrium to the ternary material can further improve the capacity and cycle performance of the ternary material.

[0035] In any embodiment, the positive electrode active material has a powder resistivity of 100 to 8000 Ω·cm at 12 MPa.

[0036] When the resistivity of the material powder is within the above range, the power performance of the material can be further improved.

[0037] In any embodiment, the tap density of the positive electrode active material is 1.9 to 2.6 g / cm 3 .

[0038] The second aspect of the present application provides a lithium secondary battery, comprising the positive electrode active material described in the first aspect of the present application.

[0039] In any embodiment, the lithium secondary battery has a gram capacity of the positive electrode active material of 193 to 210 mAh / g at 25° C. and a 1 / 3C discharge rate.

[0040] In any embodiment, the lithium secondary battery has a gram capacity of the positive electrode active material of 202 to 210 mAh / g at 25° C. and a 1 / 3C discharge rate.

[0041] The third aspect of the present application provides an electrical device, comprising the lithium secondary battery described in the second aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1A and Figure 1B This is a single crystal morphology of the positive electrode active material prepared in Example 1.

[0043] Figure 2 This is a polycrystalline morphology of the positive electrode active material prepared in Example 1.

[0044] Figure 3 Schematic diagram of a secondary battery according to one embodiment of the present application.

[0045] Figure 4 yes Figure 3 An exploded view of a secondary battery according to an embodiment of the present application is shown.

[0046] Figure 5 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.

[0047] Description of reference numerals:

[0048] 5 secondary battery; 51 housing; 52 electrode assembly; 53 cover plate. DETAILED DESCRIPTION

[0049] The following describes in detail the embodiments of the positive electrode active material, secondary battery, electric device and method for manufacturing the same of the present application. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0050] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0051] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0052] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0053] If not otherwise specified, all steps of the present application may be performed sequentially or randomly, and may be performed sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0054] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0055] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0056] At present, improving the energy density of materials has become the main research direction for the development of positive electrode active materials, and increasing nickel and capacity is one of the commonly used methods. However, with the increase of nickel content in ternary materials, the phase change of the material is intensified and the lattice shrinkage and expansion rate increases, which causes the cycle life of the material to deteriorate. The present application provides a positive electrode active material having good structural stability and gram capacity, so that the prepared battery can take into account good energy density and cycle performance.

[0057] [Positive electrode active material]

[0058] In order to achieve the above-mentioned purpose, the present application provides a positive electrode active material containing transition metal elements, wherein the positive electrode active material includes: a nickel element, wherein the molar proportion of the nickel element in the total amount of nickel, cobalt and manganese metal elements is more than 55%; a cobalt element, wherein the molar proportion of the cobalt element in the total amount of nickel, cobalt and manganese metal elements is less than 20%; a first modifying element Zr; a second modifying element Al; a third modifying element B; and a fourth modifying element: which is at least one of Nb, Mo and W; wherein, based on the total mass of the positive electrode active material, the mass proportion of the first modifying element is 0.01% to 0.5%, the mass proportion of the second modifying element is 0.01% to 1%, the mass proportion of the third modifying element is 0.01% to 0.4%, and the mass proportion of the fourth modifying element is 0.01% to 2.2%.

[0059] In ternary materials, as the proportion of nickel content in transition metals increases, the energy density of the material becomes higher and higher, but the higher energy density reduces the electrochemical stability of the material. In the technical solution of the present application, by adding modifying elements to the ternary material and coupling a variety of different modifying elements with the ternary material, the capacity and cycle performance of the ternary material can be greatly improved. Among them, the first modifying element and the second modifying element can react with the bulk phase of the ternary material, which helps to improve the structural stability of the material and optimize the transmission of lithium ions, and also helps to reduce the side reactions between the ternary material and the electrolyte, thereby significantly improving the cycle stability and power performance of the material. At the same time, the third modifying element and the fourth modifying element can increase the capacity of the material, so that the ternary material can achieve high capacity. When the mass ratio of these four modifying elements is matched within the above range, the positive electrode active material can take into account both good capacity and stability, and the battery prepared therefrom can take into account both good energy density and cycle performance.

[0060] In some embodiments, the positive electrode active material includes: nickel element, the molar proportion of the nickel element in the total amount of nickel, cobalt, and manganese elements is 55% or more, such as 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, etc., or other unlisted values ​​above 55%. In some preferred embodiments, the molar proportion of the nickel element in the total amount of nickel, cobalt, and manganese elements is 60%, 80%, or 95%.

[0061] In some embodiments, the positive electrode active material further comprises: cobalt element, the molar proportion of the cobalt element in the total amount of nickel, cobalt and manganese elements is less than 20%, such as 2%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, or other unlisted values ​​less than 20%. In some preferred embodiments, the molar proportion of the cobalt element in the total amount of nickel, cobalt and manganese elements is 3% or 10%.

[0062] In some embodiments, the positive electrode active material further includes: a first modifying element Zr; a second modifying element Al; a third modifying element B; and a fourth modifying element: which is at least one of Nb, Mo, and W.

[0063] In some embodiments, based on the total mass of the positive electrode active material, the mass proportion of the first modifying element is 0.01% to 0.5%, such as 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, or other unlisted values ​​within the range of 0.01% to 0.5%. In some preferred embodiments, the mass proportion of the first modifying element is 0.01%, 0.5%.

[0064] In some embodiments, based on the total mass of the positive electrode active material, the mass proportion of the second modifying element is 0.01% to 1%, such as 0.01%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, or other unlisted values ​​within the range of 0.01% to 1%. In some preferred embodiments, the mass proportion of the second modifying element is 0.0.1%, 0.05%, 0.3%, 1%.

[0065] In some embodiments, based on the total mass of the positive electrode active material, the mass proportion of the third modifying element is 0.01% to 0.4%, such as 0.01%, 0.1%, 0.2%, 0.3%, 0.4%, or other unlisted values ​​within the range of 0.01% to 0.4%. In some preferred embodiments, the mass proportion of the third modifying element is 0.01%, 0.1%, 0.2%, 0.4%.

[0066] In some embodiments, based on the total mass of the positive electrode active material, the mass proportion of the fourth modified element is 0.01% to 2.2%, such as 0.2%, 0.4%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, 2.2%, or other unlisted values ​​within the range of 0.01% to 2.2%. In some preferred embodiments, the mass proportion of the fourth modified element is 0.01%, 0.3%, 2.0%, or 2.2%.

[0067] In some embodiments, in the positive electrode active material, the mass ratio of (first modified element + second modified element): (third modified element + fourth modified element) is 1: (0.1-10), for example, 1: 1, 1: 2, 1: 3, 1: 4, 1: 5, 1: 6, 1: 7, 1: 8, 1: 9, 1: 10, or other unlisted values ​​within the range of 1: (0.1-10). In some preferred embodiments, in the positive electrode active material, the mass ratio of (first modified element + second modified element): (third modified element + fourth modified element) is 1: 0.625, 1: 0.5, 1: 3, 1: 0.91, 1: 0.33, 1: 2.75, 1: 0.3875, 1: 0.875, 1: 1.61, 1: 0.15, 1: 0.98, 1: 0.2, 1: 1.625, 1: 0.26.

[0068] In some embodiments, in the positive electrode active material, the mass ratio of (first modifying element+second modifying element):(third modifying element+fourth modifying element) is 1:(0.33-3).

[0069] In some embodiments, in the positive electrode active material, the mass ratio of (first modifying element+second modifying element):(third modifying element+fourth modifying element) is 1:(0.1-0.5).

[0070] In some embodiments, in the positive electrode active material, the mass ratio of the first modifying element: the second modifying element is 1: (0.1-30), for example, 1: 1, 1: 2, 1: 3, 1: 4, 1: 5, 1: 6, 1: 7, 1: 8, 1: 9, 1: 10, 1: 15, 1: 20, 1: 25, 1: 30, or other unlisted values ​​within the range of 1: (0.1-30). In some preferred embodiments, in the positive electrode active material, the mass ratio of the first modifying element: the second modifying element is 1: 0.6, 1: 0.1, 1: 2, 1: 30, 1: 0.1, 1: 0.02, 1: 4.

[0071] In some embodiments, in the positive electrode active material, the mass ratio of the first modifying element: the second modifying element is 1:(0.1-2).

[0072] In some embodiments, in the positive electrode active material, the mass ratio of the first modifying element: the second modifying element is 1:(0.1-1).

[0073] In some embodiments, in the positive electrode active material, the mass ratio of the third modified element to the fourth modified element is 1:(0.05-30), such as 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:15, 1:20, 1:25, 1:30, or other unlisted values ​​within the range of 1:(0.05-30). In some preferred embodiments, in the positive electrode active material, the mass ratio of the third modified element to the fourth modified element is 1:1.5, 1:3, 1:11, 1:1, 1:10, 1:30, 1:0.75, 1:0.3, 1:0.05.

[0074] In some embodiments, in the positive electrode active material, the mass ratio of the third modifying element to the fourth modifying element is 1:(1-10).

[0075] In some embodiments, in the positive electrode active material, the mass ratio of the third modifying element: the fourth modifying element is 1:(0.1-1).

[0076] In some embodiments, the fourth modifying element is W. In some embodiments, in the positive electrode active material, the mass ratio of (element Zr + element Al): (element B + element W) is 1:(0.1-0.5), for example, 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, or other unlisted values ​​within the range of 1:(0.1-0.5).

[0077] In some embodiments, in the positive electrode active material, the mass ratio of element Zr:element Al is 1:(0.1-1), for example 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, or other unlisted values ​​within the range of 1:(0.1-1).

[0078] In some embodiments, the fourth modifying element is W. In some embodiments, in the positive electrode active material, the mass ratio of the third modifying element B: the fourth modifying element W is 1:(0.1-1), for example, 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, or other unlisted values ​​within the range of 1:(0.1-1).

[0079] By further precisely controlling the mass ratios of the first modifying element, the second modifying element, the third modifying element, and the fourth modifying element, the electrochemical properties and stability of the positive electrode active material can be further optimized to achieve the optimal solution for material performance.

[0080] In some embodiments, based on the total mass of the positive electrode active material, the mass of the first modifying element accounts for 0.05% to 0.5%.

[0081] In some embodiments, based on the total mass of the positive electrode active material, the mass of the second modifying element accounts for 0.05% to 0.3%.

[0082] In some embodiments, based on the total mass of the positive electrode active material, the mass of the third modifying element accounts for 0.01% to 0.2%.

[0083] In some embodiments, based on the total mass of the positive electrode active material, the mass of the fourth modifying element accounts for 0.01% to 0.3%.

[0084] When the mass ratios of the first modifying element, the second modifying element, the third modifying element, and the fourth modifying element are within the above ranges, the energy density and cycle performance of the material can be further improved.

[0085] In some embodiments, the molar ratio of the nickel element in the total amount of nickel, cobalt and manganese elements is 60% to 95%.

[0086] In some embodiments, the molar ratio of the nickel element in the total amount of nickel, cobalt and manganese metal elements is 80% to 95%.

[0087] In some embodiments, the molar ratio of the cobalt element in the total amount of nickel, cobalt and manganese elements is 3% to 10%.

[0088] When the ratio of nickel and cobalt to transition metal in the positive electrode active material is within the above range, the material has a better gram capacity, and the battery prepared therefrom can better balance energy density and cycle performance.

[0089] In some embodiments, the positive active material includes single crystal particles and polycrystalline particles.

[0090] As used herein, "single crystal" means a complete particle, or an agglomerate of 2 to 9 primary particles, or an agglomerate of 10 to 49 primary particles, or a mixture of the above types of particles and / or agglomerates, see Appendix Figure 1A and 1B .

[0091] As used herein, "polycrystalline" refers to secondary particles formed by the agglomeration of multiple primary particles, where "multiple" generally refers to more than 10, more than 50, more than 100, or a mixture of the above types of agglomerates, see Appendix Figure 2 .

[0092] When used in this article, when the terms "single crystal" and "polycrystalline" appear at the same time, "single crystal" refers to particles with polygonal or irregular outer contours, see Appendix Figure 1A and 1B ; “polycrystalline” refers to particles with a circular or nearly circular outer contour, see Appendix Figure 2 .

[0093] When the positive electrode active material includes both single crystal particles and polycrystalline particles, the single crystal mixed polycrystalline system is beneficial to further improve the volume energy density and cycle stability of the material compared with a single particle type system.

[0094] In some embodiments, the specific surface area of ​​the single crystal particles is 0.9 to 1.5 m 2 / g, for example 0.9m 2 / g, 1.0m 2 / g, 1.1m 2 / g, 1.2m 2 / g, 1.3m 2 / g, 1.4m 2 / g, 1.5m 2 / g, or 0.9~1.5m 2 In some preferred embodiments, the specific surface area of ​​the single crystal particles is 0.9 to 1.2 m 2 In some preferred embodiments, the specific surface area of ​​the single crystal particles is 0.9 m 2 / g.

[0095] In some embodiments, the specific surface area of ​​the polycrystalline particles is 0.3 to 1.0 m 2 / g, for example 0.3m 2 / g, 0.4m 2 / g, 0.5m 2 / g, 0.6m 2 / g, 0.7m 2 / g, 0.8m 2 / g, 0.9m 2 / g, 1.0m 2 / g, or 0.3~1.0m 2 In some preferred embodiments, the specific surface area of ​​the polycrystalline particles is 0.3 m 2 / g, 0.5m 2 / g, 1.0m 2 / g.

[0096] As used in this article, "specific surface area" refers to the total area per unit mass of a material. The determination method can refer to GB / T19587-2017, using the nitrogen adsorption specific surface area analysis test method and calculated using the BET (Brunauer Emmett Teller) method, where the nitrogen adsorption specific surface area analysis test can be performed using the Tri-Star 3020 specific surface area pore size analysis tester from Micromeritics, USA.

[0097] When the specific surface area of ​​the positive electrode active material is within the above range, it is beneficial to increase the contact area between the positive electrode material and the electrolyte, so that the electrochemical activity of the material is further enhanced.

[0098] In some embodiments, in the positive electrode active material, the mass ratio of the single crystal particles to the polycrystalline particles is 1:9 to 5:5, for example, 1:9, 2:8, 3:7, 4:6, 5:5, or other unlisted values ​​within the range of 1:9 to 5:5.

[0099] In some embodiments, in the positive electrode active material, a mass ratio of the single crystal particles to the polycrystalline particles is 1:9 to 3:7.

[0100] In some embodiments, the volume average particle size Dv50 of the single crystal particles is 3 to 5 μm, for example, 3.0 μm, 3.5 μm, 4.0 μm, 4.5 μm, 5.0 μm, or other unlisted values ​​within the range of 3 to 5 μm. In some preferred embodiments, the volume average particle size Dv50 of the single crystal particles is 4 μm.

[0101] In some embodiments, the volume average particle size Dv50 of the polycrystalline particles is 4 to 13 μm, such as 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, or other values ​​not listed in the range of 4 to 13 μm. In some preferred embodiments, the volume average particle size Dv50 of the polycrystalline particles is 4 μm, 10 μm, or 13 μm.

[0102] As used herein, "volume average particle size Dv50" refers to the particle size corresponding to the cumulative volume distribution percentage reaching 50% in the particle size distribution of particles, starting from the small particle size side. The determination method can refer to GB / T19077-2016 / ISO 13320:2009 and is measured using Malvern 2000 (MasterSizer 2000) laser particle size analyzer.

[0103] When the single crystal particles and the polycrystalline particles in the positive electrode active material are matched in the above-mentioned mass ratio and particle size, the energy density and cycle performance of the battery can be further improved.

[0104] In some embodiments, the positive electrode active material has a molecular formula Li a (Ni b Co c Mn 1-b-c ) 1-x-y-z- q Zr x Al y B z Q q O e , wherein Q includes at least one of Nb, Mo, and W, 0.9≤a≤1.2, 0.55≤b≤0.95, 0≤c≤0.20, 1.8≤e≤2.2, 0≤x≤0.04, 0≤y≤0.02, 0≤z≤0.09, and 0≤q≤0.03.

[0105] When used in this article, "having a molecular formula" is not limited to the substance represented by the molecular formula, but also includes other substances formed after further appropriate modification on the basis of the molecular formula, which is not limited here. The use of "having a molecular formula" is only for the convenience of description and is not intended to limit this application. It can be understood that new materials or new substances obtained by appropriate modification on the basis of the listed positive active materials are also within the scope of positive active materials. The aforementioned appropriate modification refers to acceptable modification methods for positive active materials, and non-limiting examples include coating modification.

[0106] In the enumeration of positive electrode active materials in this application, unless otherwise specified, the Li content is the initial state of the material. The positive electrode active material is applied to the positive electrode plate in the battery system. After the charge and discharge cycle, the Li content in the positive electrode active material contained in the positive electrode plate usually changes. Among them, the Li content can be measured by atomic molar content, but is not limited to this. Regarding "the Li content is the initial state of the material", the initial state of the material refers to the state before the material is added to the positive electrode slurry.

[0107] In the list of positive electrode active materials in this application, the content of oxygen (O) is only a theoretical state value. The release of oxygen from the lattice will cause the atomic molar content of oxygen to change, and the actual content of O will fluctuate. Among them, the content of O can be measured by atomic molar content, but is not limited to this.

[0108] In some embodiments, the positive electrode active material also includes strontium (Sr), and the mass proportion of the strontium element is 0.05% to 0.2%, based on the total mass of the positive electrode active material, for example, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%, or other unlisted values ​​within the range of 0.05% to 0.2%.

[0109] In some embodiments, the positive electrode active material also includes yttrium element (Y), and the mass proportion of the yttrium element is 0.05% to 0.2% based on the total mass of the positive electrode active material, for example, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%, or other unlisted values ​​within the range of 0.05% to 0.2%.

[0110] Further adding modifying elements such as strontium and / or yttrium to the ternary material can further improve the capacity and cycle performance of the ternary material.

[0111] In some embodiments, the powder resistivity of the positive electrode active material at 12 MPa is 100 to 8000 Ω·cm, such as 100 Ω·cm, 500 Ω·cm, 1000 Ω·cm, 1500 Ω·cm, 2000 Ω·cm, 2500 Ω·cm, 3000 Ω·cm, 3500 Ω·cm, 4000 Ω·cm, 4500 Ω·cm, 5000 Ω·cm, 6000 Ω·cm, 7000 Ω·cm, 8000 Ω·cm, or other values ​​not listed in the range of 100 to 8000 Ω·cm. In some preferred embodiments, the powder resistivity of the positive electrode active material at 12 MPa is 2000 Ω·cm, 1500 Ω·cm, 2200 Ω·cm, 1900 Ω·cm, 8000 Ω·cm, 1600 Ω·cm, 100 Ω·cm, 5000 Ω·cm.

[0112] As used in this article, "powder resistivity" is a parameter that describes the conductive properties of powder materials, usually referring to the resistance per unit length or unit area, measured in ohm-centimeter (Ω-cm). The determination method is based on the standard GB / T 30835-2014, using a powder resistivity tester (ST2722) for testing.

[0113] When the resistivity of the material powder is within the above range, the power performance of the material can be further improved.

[0114] In some embodiments, the tap density of the positive electrode active material is 1.9 to 2.6 g / cm 3 , for example 1.9 g / cm 3 , 2.0g / cm 3 , 2.1g / cm 3 , 2.2g / cm 3 , 2.3g / cm 3 , 2.4g / cm 3 , 2.5g / cm 3 , 2.6g / cm 3 , or 1.9~2.6g / cm 3 In some preferred embodiments, the tap density of the positive electrode active material is 2.52 g / cm 3 , 2.55g / cm 3 , 2.50g / cm 3 , 2.60g / cm 3 .

[0115] In some preferred embodiments, the tap density of the positive electrode active material is 2.5 to 2.6 g / cm 3 .

[0116] As used in this article, "tapped density" means: a certain amount of powder is placed in a container, vibrated and rotated by a vibration device until the volume of the powder no longer decreases, and the density is obtained by dividing the mass of the powder by the volume after tapping. The determination method can refer to GB / T5162-2006, using a powder tap density tester (such as Dandong Better BT-301) to determine the tap density with the following measurement parameters: vibration frequency 250±15 times / minute, amplitude 3±0.2mm, vibration number 5000 times, and measuring cylinder volume 25mL.

[0117] In some embodiments, the lithium secondary battery has a gram capacity of the positive electrode active material of 193 to 210 mAh / g, for example, 193 mAh / g, 194 mAh / g, 195 mAh / g, 196 mAh / g, 197 mAh / g, 198 mAh / g, 199 mAh / g, 200 mAh / g, 201 mAh / g, 202 mAh / g, 203 mAh / g, 204 mAh / g, 205 mAh / g, 206 mAh / g, 207 mAh / g, 208 mAh / g, 209 mAh / g, 210 mAh / g, or other unlisted values ​​within the range of 193 to 210 mAh / g.

[0118] In some preferred embodiments, the lithium secondary battery has a gram capacity of the positive electrode active material of 202 to 210 mAh / g at 25° C. and a 1 / 3C discharge rate.

[0119] [Positive electrode]

[0120] The present application also provides a positive electrode plate, characterized in that it includes a positive electrode collector and a positive electrode active material arranged on at least one surface of the positive electrode collector, wherein the positive electrode active material is the positive electrode active material described in the present application.

[0121] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0122] In some embodiments, the positive electrode plate may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0123] In some embodiments, the positive electrode plate may further include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0124] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0125] [Negative electrode]

[0126] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.

[0127] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0128] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0129] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0130] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0131] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0132] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0133] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0134] [Electrolytes]

[0135] The electrolyte plays a role in conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs.

[0136] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0137] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0138] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0139] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0140] [Isolation film]

[0141] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0142] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0143] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0144] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0145] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0146] [Lithium secondary battery]

[0147] The present application also provides a lithium secondary battery, characterized in that it includes the positive electrode sheet described in the present application.

[0148] The present application has no particular limitation on the shape of the lithium secondary battery, which may be cylindrical, square or any other shape. Figure 3 The secondary battery 5 is a square structure as an example.

[0149] In some embodiments, reference Figure 4 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0150] [Electrical devices]

[0151] In addition, the present application also provides an electrical device, the electrical device includes the lithium secondary battery provided in the present application. The lithium secondary battery can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0152] As the electrical device, a lithium secondary battery can be selected according to its usage requirements.

[0153] Figure 5 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the power consumption device's requirements for high power and high energy density of lithium secondary batteries, a battery pack or a battery module can be used.

[0154] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a lithium secondary battery may be used as a power source.

[0155] Example

[0156] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0157] 1. Preparation method

[0158] Example 1

[0159] 1.1. Preparation of positive electrode active materials

[0160] (1) Polycrystalline preparation method:

[0161] The ternary polycrystalline precursor (Ni 0.80 Co 0.10 Mn 0.10 )OH2 (volume average particle size Dv50 = 10 μm), LiOH·H2O, ZrO2, Al2O3, and MoO3 are mixed in a mixer at the molar ratio of the corresponding elements in the molecular formula, and then sintered at 800°C in an oxygen atmosphere (oxygen volume concentration>99.9%) for 20 h to obtain material 1, which is mechanically crushed and washed in deionized water (material-liquid mass ratio 0.5:1 to ensure that the material does not sink to the bottom during stirring) for 1 min.

[0162] Then, the washed material 1 is mixed with H3BO3 in the molar ratio of the corresponding elements in the molecular formula, and sintered at 400°C for 10 hours in an oxygen atmosphere (oxygen volume concentration>99.9%) to obtain a polycrystalline positive electrode active material. The molecular formula of the obtained polycrystalline positive electrode active material is Li(Ni 0.8 Co 0.1 Mn 0.1 ) 0.963 Zr 0.005 Al 0.011 B 0.018 Mo 0.003 O2, with a specific surface area of ​​0.5m 2 / g, and the volume average particle size Dv50 is 10 μm.

[0163] (2) Single crystal preparation method:

[0164] The ternary single crystal precursor (Ni 0.80 Co 0.10 Mn 0.10)OH2 (volume average particle size Dv50 = 3 μm), LiOH·H2O, ZrO2, Al2O3, and MoO3 are mixed in a mixer at the molar ratio of the corresponding elements in the molecular formula, and then sintered at 850°C for 25 h in an oxygen atmosphere (oxygen volume concentration > 99.9%), and crushed by air flow to obtain material 2.

[0165] Then, material 2 and H3BO3 were mixed in the molar ratio of the corresponding elements in the molecular formula, and sintered at 400°C for 10 hours in an oxygen atmosphere (oxygen volume concentration>99.9%) to obtain a single crystal positive electrode active material. The molecular formula of the obtained single crystal positive electrode active material is Li(Ni 0.8 Co 0.1 Mn 0.1 ) 0.963 Zr 0.005 Al 0.011 B 0.018 Mo 0.003 O2, with a specific surface area of ​​0.9m 2 / g, and the volume average particle size Dv50 is 4 μm.

[0166] (3) Preparation method of polycrystalline mixed single crystal:

[0167] The polycrystalline positive electrode active material and the single crystal positive electrode active material are physically mixed in a mass ratio of 5:5 to obtain a polycrystalline mixed single crystal positive electrode active material. The powder resistivity of the obtained polycrystalline mixed single crystal positive electrode active material at 12 MPa is 2000 Ω·cm.

[0168] 1.2. Preparation of positive electrode

[0169] The positive electrode active material of the polycrystalline mixed single crystal prepared in 1.1, polyvinylidene fluoride and conductive carbon black are mixed in a mass ratio of 90:5:5, and then N-methylpyrrolidone (NMP) is added and stirred for 2 hours. Then, it is stirred in a homogenizer at 1200r / min until it is evenly mixed, and then evenly coated on the double-side surface of a 13-micron thick aluminum foil current collector. After coating, it is dried in a drying oven at 120°C, cold pressed, and cut to obtain positive electrode sheets.

[0170] 1.3. Preparation of electrolyte

[0171] A mixed solution of ethylene carbonate (EC) and diethyl carbonate (DEC) was mixed in a volume ratio of 1:2 to obtain a mixed solvent. Then, in an argon atmosphere glove box, fully dried lithium hexafluorophosphate was dissolved in the mixed solvent and mixed evenly to obtain an electrolyte. The lithium salt concentration in the electrolyte was 1 mol / L.

[0172] 1.4. Preparation of negative electrode

[0173] The negative electrode active material graphite, sodium carboxymethyl cellulose, styrene butadiene rubber and acetylene black are mixed in a mass ratio of 96:1:1:2, deionized water is added, and the mixture is stirred evenly in a blender. The slurry is then coated on both sides of an 8-micron thick copper foil, dried in an oven at 120°C, cold pressed, and cut to obtain negative electrode sheets.

[0174] 1.5. Preparation of battery cells

[0175] The positive electrode sheet, isolation film, and negative electrode sheet are stacked from top to bottom, ensuring that the positive and negative electrode sheets cannot touch each other. Then they are wound into bare cells through a winding needle, placed in a square aluminum shell, and injected with electrolyte. The cells are prepared by steps of standing, forming, and capacity.

[0176] Examples 2 to 20 and 22

[0177] The secondary batteries of Examples 2 to 20 and 22 are prepared in a similar manner to that of Example 1, but the type and content of the elements in the positive electrode active material are adjusted, or the BET and powder resistivity of the positive electrode active material are adjusted, or the mass ratio of single crystal particles in the positive electrode active material, DV50 (single crystal particles, polycrystalline particles), and the tap density of the positive electrode active material are adjusted. The different preparation parameters are detailed in Tables 1 to 5. According to the types and mass proportions of different elements in Tables 1 to 5, the chemical formulas of the positive electrode active materials prepared in Examples 2 to 20 and 22 can be converted.

[0178] Embodiment 21

[0179] The secondary battery of Example 21 is prepared in a similar manner to that of Example 1, but the types of raw materials are adjusted to change the types of elements in the positive electrode active material. The difference between the preparation method of Example 21 and that of Example 1 is as follows:

[0180] (1) Polycrystalline preparation method:

[0181] The ternary polycrystalline precursor (Ni 0.80 Co 0.10 Mn 0.10 )OH2 (volume average particle size Dv50 = 10 μm), LiOH·H2O, ZrO2, Al2O3, MoO3, SrO, and Y2O3 are mixed in a mixer in the molar ratio of the corresponding elements in the molecular formula, and then the same preparation steps as in Example 1 are carried out.

[0182] (2) Single crystal preparation method:

[0183] The ternary single crystal precursor (Ni 0.80 Co 0.10 Mn 0.10)OH2 (volume average particle size Dv50 = 3 μm), LiOH·H2O, ZrO2, Al2O3, MoO3, SrO, and Y2O3 are mixed in a mixer in the molar ratio of the corresponding elements in the molecular formula, and then the same preparation steps as in Example 1 are carried out.

[0184] Other different preparation parameters are detailed in Tables 1 to 5. According to the types and mass proportions of different elements in Tables 1 to 5, the chemical formula of the positive electrode active material prepared in Example 21 can be converted.

[0185] Comparative Examples 1 to 6

[0186] The secondary batteries of Comparative Examples 1 to 6 were prepared in a similar manner to that of Example 1, but the types and contents of the modifying elements in the positive electrode active materials were adjusted. The different preparation parameters are detailed in Tables 1 to 5.

[0187] 2. Performance Test

[0188] 1. Test methods for parameters related to positive electrode active materials

[0189] (1) Material composition test method

[0190] Inductively coupled plasma optical emission spectrometry was used, and the specific testing equipment was an inductively coupled plasma optical emission spectrometer model iCAP 7400 from Thermo Scientific.

[0191] (2) BET specific surface area test method

[0192] The nitrogen adsorption specific surface area analysis test method is used for testing, and the result is calculated by the BET (Brunauer Emmett Teller) method. The nitrogen adsorption specific surface area analysis test can be performed by a TriStar II specific surface and pore analyzer of Micromeritics Corporation of the United States. The test steps can refer to GB / T 19587-2004.

[0193] The detailed steps are as follows: dry the sample to be tested in a vacuum drying oven at 200°C for 2 hours; weigh 1g of the sample to be tested and place it in a test tube, fill the liquid nitrogen cup with liquid nitrogen, insert it into the test tube, use nitrogen as the adsorption gas, and use a specific surface and pore analyzer to map the adsorption-desorption curve with a relative pressure P / P0 of 0 to 0.99, where P is the equilibrium adsorption pressure and P0 is the saturated vapor pressure. The BET specific surface area of ​​the positive electrode active material is calculated by the BET method.

[0194] (3) Powder resistivity test method

[0195] On a four-probe powder resistivity meter, 2.4 g of positive electrode active material was placed in a feeding cup, a pressure of 12 MPa was applied, and the powder resistivity of the material was recorded.

[0196] (4) Scanning electron microscope test method

[0197] The positive electrode material is tested by SEM to obtain the microscopic morphology of the material.

[0198] (5) Volume average particle size Dv50 test method

[0199] Equipment model: Malvern 2000 (MasterSizer 2000) laser particle size analyzer, reference standard process: GB / T19077-2016 / ISO 13320:2009.

[0200] Detailed test process: Take an appropriate amount of washed sample (the sample concentration ensures 8% to 12% shading), add 20mL of anhydrous ethanol, and ultrasonically treat for 5 minutes (53KHz / 120W) to ensure that the sample is completely dispersed, and then measure the sample according to GB / T19077-2016 / ISO13320:2009 standard.

[0201] (6) Tap density test method

[0202] Using Dandong BT-300 and a 25ml measuring cylinder, fill the material to 20ml, and then use a vibration number of 5000 and a vibration frequency of 250 times / min to measure the tap density of the material.

[0203] (7) Pole compaction density test method

[0204] 1) Cut the above positive electrode sheet into a film sheet with a length of 1000 mm;

[0205] 2) The positive electrode film is rolled with a certain pressure. Since the aluminum foil has ductility, the length of the film is 1006mm;

[0206] 3) Punching area is 1540.25mm 2 The weight and thickness of the small disc are measured, and the compaction density can be calculated as (small disc weight - substrate weight) / 1540.25 / (coating thickness - substrate thickness).

[0207] 2. Battery performance test method

[0208] (1) Gram capacity test method

[0209] At 25°C, first discharge at 1 / 3C rate to 2.80V, hold for 30min, then charge at 1 / 3C rate to 4.25V with constant current, then discharge at 1 / 3C rate to 2.80V, and record the discharge capacity of the first cycle of the corresponding battery as C0. Finally, divide C0 by the mass of the positive electrode active material to get the gram capacity.

[0210] (2) Cyclic performance test method

[0211] At 25°C, the battery is charged at a constant current of 1 / 3C to a voltage of 4.25V, then charged at a constant voltage of 4.25V to a rate of 0.05C, and discharged at a rate of 1 / 3C to a voltage of 2.80V, which is the first cycle. The discharge capacity of the first cycle is recorded as C0; the cycle is repeated as above, and the discharge capacity of the nth cycle is recorded as Cn. The capacity retention rate of each cycle is Cn / C0*100%, and the capacity retention rate after 100 cycles is calculated.

[0212] III. Analysis of test results of various embodiments and comparative examples

[0213] The batteries of the embodiments and comparative examples were prepared according to the above method, and various performance parameters were measured. The results are shown in Table 5 below.

[0214] Table 1 Preparation parameters

[0215]

[0216] Table 2 Preparation parameters

[0217]

[0218] Table 3 Preparation parameters

[0219]

[0220] Table 4 Preparation parameters

[0221]

[0222] Table 5 Preparation parameters and performance parameters

[0223]

[0224] The first modifying element Zr, the second modifying element Al, the third modifying element B, and the fourth modifying element (at least one of Nb, Mo, and W) are added to the positive electrode active materials in Examples 1 to 22, and the batteries prepared therefrom have excellent gram capacity and cycle performance.

[0225] No modifying element is added to the positive electrode active material of Comparative Example 1. From the comparison between Comparative Example 1 and Examples 1 to 22, it can be seen that adding the first modifying element Zr, the second modifying element Al, the third modifying element B, and the fourth modifying element (at least one of Nb, Mo, and W) to the positive electrode active material can effectively increase the gram capacity of the positive electrode active material and improve the cycle performance of the lithium secondary battery.

[0226] Only the first modifying element Zr and the second modifying element Al were added to the positive electrode active material of Comparative Example 2, only the third modifying element B and the fourth modifying element Mo were added to the positive electrode active material of Comparative Example 3, and only the first modifying element Zr, the second modifying element Al, and the fourth modifying element Mo were added to the positive electrode active material of Comparative Example 6. From the comparison between Comparative Examples 2 to 3 and 6 and Examples 1 to 22, it can be seen that adding four modifying elements to the positive electrode active material at the same time can effectively increase the gram capacity of the positive electrode active material and improve the cycle performance of the lithium secondary battery; while when only two or three of the four modifying elements are added to the positive electrode active material, the improvement of the overall performance of the battery is limited.

[0227] It can be seen from Examples 1 to 6 that when the mass ratio of (first modifying element + second modifying element): (third modifying element + fourth modifying element) in the positive electrode active material is controlled to be 1:(0.1 to 10), or when the mass ratio of the first modifying element: the second modifying element is controlled to be 1:(0.1 to 30), or when the mass ratio of the third modifying element: the fourth modifying element is controlled to be 1:(0.05 to 30), the positive electrode active material can have a higher gram capacity and the lithium secondary battery can have excellent cycle performance.

[0228] It can be seen from Examples 1 to 22 that, based on the total mass of the positive electrode active material, when the mass proportion of the first modifying element is controlled to be 0.01% to 0.5%, or when the mass proportion of the second modifying element is controlled to be 0.01% to 1%, or when the mass proportion of the third modifying element is controlled to be 0.01% to 0.4%, or when the mass proportion of the fourth modifying element is controlled to be 0.01% to 2.2%, the positive electrode active material can have a higher gram capacity and the lithium secondary battery can have excellent cycle performance.

[0229] In the positive electrode active material of Comparative Example 4, the mass proportion of the first modified element exceeds the range of 0.01% to 0.5%, and the mass proportion of the second modified element exceeds the range of 0.01% to 1%. In the positive electrode active material of Comparative Example 5, the mass proportion of the third modified element exceeds the range of 0.01% to 0.4%, and the mass proportion of the fourth modified element exceeds the range of 0.01% to 2.2%. From the comparison of Comparative Examples 4 to 5 with Examples 1 to 22, it can be seen that when the mass proportion of the modified elements in the positive electrode active material is controlled within a certain range, the gram capacity of the positive electrode active material can be effectively improved, and the cycle performance of the lithium secondary battery can be improved; when the mass proportion of the modified element exceeds the above range, the improvement in battery performance is small.

[0230] It can be seen from Examples 1 and 7 to 8 that when various types of fourth modifying elements (such as Nb, Mo, and W) are added to the positive electrode active material, the batteries prepared therefrom have excellent gram capacity and cycle performance.

[0231] As can be seen from Examples 1, 9 to 11, when the molar ratio of nickel in the total amount of transition metal elements in the positive electrode active material is above 55% (preferably within the range of 60% to 95%), the batteries prepared therefrom have excellent gram capacity and cycle performance. At the same time, when the molar ratio of cobalt in the total amount of transition metal elements in the positive electrode active material is below 20% (preferably within the range of 3% to 10%), the batteries prepared therefrom have excellent gram capacity and cycle performance.

[0232] It can be seen from Examples 1 and 21 that, on the basis of adding four modifying elements simultaneously to the positive electrode active material, further adding Sr element and Y element can further improve the cycle performance of the battery.

[0233] It can be seen from Examples 1 to 21 that the positive electrode active material adopts a single crystal mixed polycrystalline system, and the prepared battery has good gram capacity and cycle performance. Figure 2 The morphology of single crystal particles and polycrystalline particles of the positive electrode active material are shown in Figure 1. At the same time, when the mass ratio of single crystal particles to polycrystalline particles in the positive electrode active material is controlled to be 1:9 to 5:5 (preferably in the range of 1:9 to 3:7), the batteries prepared therefrom have excellent gram capacity and cycle performance.

[0234] The positive electrode active material of Example 22 only uses a single crystal system and does not contain polycrystals. From the comparison between Example 22 and Examples 1 to 21, it can be seen that the compaction density of the positive electrode active material of the single crystal system is poor compared with the single crystal mixed polycrystalline system. The use of a single crystal mixed polycrystalline system in the positive electrode active material of the present application can further improve the compaction density of the active material, thereby comprehensively improving its performance.

[0235] It can be seen from Examples 1 to 22 that the specific surface area of ​​the single crystal particles in the positive electrode active material is controlled to be 0.9 to 1.5 m 2 / g, or the specific surface area of ​​the polycrystalline particles is controlled to be 0.3-1.0m 2 / g, the batteries prepared therefrom have excellent gram capacity and cycle performance; when the powder resistivity of the positive electrode active material at 12MPa is controlled in the range of 100 to 5000Ω·cm, the batteries prepared therefrom have excellent gram capacity and cycle performance.

[0236] It should be noted that the present application is not limited to the embodiments described. The embodiments described are only examples, and the embodiments having substantially the same structure as the technical idea and exerting the same effects within the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the subject matter of the present application, other methods of applying various modifications that can be thought of by those skilled in the art to the embodiments and combining some of the constituent elements in the embodiments to construct the embodiments are also included in the scope of the present application.

Claims

1. A positive electrode active material containing a transition metal element, characterized in that: The positive electrode active material comprises: Nickel element, wherein the molar proportion of the nickel element in the total amount of nickel, cobalt and manganese metal elements is greater than 55%; Cobalt element, wherein the molar proportion of the cobalt element in the total amount of nickel, cobalt and manganese metal elements is less than 20%; The first modifying element Zr; The second modifying element is Al; a third modifying element B; and The fourth modifying element is at least one of Nb, Mo and W; Among them, based on the total mass of the positive electrode active material, the mass proportion of the first modifying element is 0.01% to 0.5%, the mass proportion of the second modifying element is 0.01% to 1%, the mass proportion of the third modifying element is 0.01% to 0.4%, and the mass proportion of the fourth modifying element is 0.01% to 2.2%.

2. The positive electrode active material according to claim 1, characterized in that In the positive electrode active material, the mass ratio of (first modifying element+second modifying element):(third modifying element+fourth modifying element) is 1:(0.1-10).

3. The positive electrode active material according to claim 2, characterized in that In the positive electrode active material, the mass ratio of (first modifying element+second modifying element):(third modifying element+fourth modifying element) is 1:(0.1-0.5).

4. The positive electrode active material according to claim 3, characterized in that In the positive electrode active material, the mass ratio of (element Zr+element Al): (element B+element W) is 1:(0.1-0.5).

5. The positive electrode active material according to claim 1, characterized in that In the positive electrode active material, the mass ratio of the first modifying element to the second modifying element is 1:(0.1-30).

6. The positive electrode active material according to claim 5, characterized in that In the positive electrode active material, the mass ratio of the first modifying element to the second modifying element is 1:(0.1-1).

7. The positive electrode active material according to claim 6, characterized in that In the positive electrode active material, the mass ratio of element Zr to element Al is 1:(0.1-1).

8. The positive electrode active material according to claim 1, characterized in that In the positive electrode active material, the mass ratio of the third modifying element to the fourth modifying element is 1:(0.05-30).

9. The positive electrode active material according to claim 8, characterized in that In the positive electrode active material, the mass ratio of the third modifying element to the fourth modifying element is 1:(0.1-1).

10. The positive electrode active material according to claim 9, characterized in that In the positive electrode active material, the mass ratio of element B:element W is 1:(0.1-1).

11. The positive electrode active material according to claim 1, characterized in that Based on the total mass of the positive electrode active material, the mass proportion of the first modifying element is 0.05% to 0.5%.

12. The positive electrode active material according to claim 1, characterized in that Based on the total mass of the positive electrode active material, the mass proportion of the second modifying element is 0.05% to 0.3%.

13. The positive electrode active material according to claim 1, characterized in that Based on the total mass of the positive electrode active material, the mass proportion of the third modifying element is 0.01% to 0.2%.

14. The positive electrode active material according to claim 1, characterized in that Based on the total mass of the positive electrode active material, the mass proportion of the fourth modifying element is 0.01% to 0.3%.

15. The positive electrode active material according to claim 1, characterized in that The molar proportion of the nickel element in the total amount of nickel, cobalt and manganese metal elements is 60% to 95%; and / or the molar proportion of the cobalt element in the total amount of nickel, cobalt and manganese metal elements is 3% to 10%.

16. The positive electrode active material according to claim 15, characterized in that The molar proportion of the nickel element in the total amount of nickel, cobalt and manganese metal elements is 80% to 95%.

17. The positive electrode active material according to claim 1, characterized in that The positive electrode active material includes single crystal particles and polycrystalline particles.

18. The positive electrode active material according to claim 17, characterized in that The specific surface area of ​​the single crystal particles is 0.9 to 1.5 m 2 / g, the specific surface area of ​​the polycrystalline particles is 0.3 to 1.0 m 2 / g.

19. The positive electrode active material according to claim 17, characterized in that In the positive electrode active material, the mass ratio of the single crystal particles to the polycrystalline particles is 1:9 to 5:

5.

20. The positive electrode active material according to claim 17, characterized in that The volume average particle size Dv50 of the single crystal particles is 3 to 5 μm, and the volume average particle size Dv50 of the polycrystalline particles is 4 to 13 μm.

21. The positive electrode active material according to any one of claims 1 to 20, characterized in that The positive electrode active material has a molecular formula of Li a (Ni b Co c Mn 1-b-c ) 1-x-y-z-q Zr x Al y B z Q q O e , wherein Q includes at least one of Nb, Mo, and W, 0.9≤a≤1.2, 0.55≤b≤0.95, 0≤c≤0.20, 1.8≤e≤2.2, 0 <x≤0.04,0<y≤0.02,0<z≤0.09,0<q≤0.03。 22. The positive electrode active material according to claim 21, characterized in that The positive electrode active material further includes strontium (Sr), and based on the total mass of the positive electrode active material, the mass proportion of the strontium is 0.05% to 0.2%.

23. The positive electrode active material according to claim 21, characterized in that The positive electrode active material further includes yttrium element (Y). Based on the total mass of the positive electrode active material, the mass proportion of the yttrium element is 0.05% to 0.2%.

24. The positive electrode active material according to any one of claims 1 to 20, characterized in that The powder resistivity of the positive electrode active material at 12 MPa is 100 to 8000 Ω·cm.

25. The positive electrode active material according to any one of claims 1 to 20, characterized in that The tap density of the positive electrode active material is 1.9 to 2.6 g / cm 3 .

26. A lithium secondary battery, characterized in that: The invention comprises the positive electrode active material according to any one of claims 1 to 25.

27. The lithium secondary battery according to claim 26, characterized in that: The lithium secondary battery has a gram capacity of the positive electrode active material of 193 to 210 mAh / g at 25° C. and a 1 / 3C discharge rate.

28. The lithium secondary battery according to claim 26, characterized in that: The lithium secondary battery has a gram capacity of the positive electrode active material of 202 to 210 mAh / g at 25° C. and a 1 / 3C discharge rate.

29. An electrical device, characterized in that: A lithium secondary battery comprising the lithium secondary battery according to any one of claims 26 to 28.

Citation Information

Patent Citations

  • Positive electrode active material for secondary battery, method for preparing same and lithium secondary battery comprising same

    CN110352518A

  • Positive electrode active material and lithium ion battery

    CN115548334A

  • Secondary battery and electric device

    CN117254117A

  • Lithium transition metal based compound powder, its manufacturing method, and positive electrode material for lithium secondary battery and lithium secondary battery using it

    JP2011108554A

  • Composite positive electrode material, preparation method therefor, secondary battery, battery module, battery pack and electrical apparatus

    WO2024020795A1

Cited By

  • Lithium-ion battery and electrical device

    WO2026157972A1